Efeitos da adubação no rendimento industrial do sorgo sacarino cultivado em solo de fertilidade construída - Scavazza, Ana Lúcia (Universidade Federal de São Carlos, 2019)
The sweet sorghum (Sorghum bicolor (L.) Moench), a poaceae originating in Eastern Central of Africa, has great potential for the production of bioenergy. In Brazil, due to the importance of sugarcane as a source of renewable energy, research on the agricultural and industrial processes of sorghum is still incipient. The objective of this dissertation was to test the hypothesis that the practice of fertilization in soil with improved fertility built influences the growth and maturation of sweet sorghum, in order to that what of promoting variations in the optimum point of harvest. The experiment was conducted in an experimental field of the Federal University of São Carlos (UFSCar), in a randomized complete block design with five blocks. The treatments were composed of four doses of fertilization, 0, 0.5, 1.0 and 1.5 of the recommended dose-RD (110-80-120 kg ha-1) of NPK for the cultivation of hybrid sweet sorghum Malibu 5010 under the conditions of the state of São Paulo, and for four harvest seasons: 90,105,120 and 135 days after the emergency (DAE). Biometric parameters were determined [height (m), diameter of the stem (mm), number of internodes (nodes plant-1), production of stems (t ha-1), biomass (t ha-1), dry biomass (t ha-1), dry mass of panicle (g m-1)], technological [brix of broth (%), Pol of broth (%), fiber (%), purity (%), RS (%), RTS (kg t-1)], productivity [yield of stalks (PC, t ha-1)], besides the accumulation of NPK for the calculation of indices of nutritional efficiency .Data were collected on the soil fertility of sugarcane reform areas to determine the fertility level and to propose the viability of sorghum cultivation with reduced doses of macronutrients. The increase of fertilization in built fertility soil did not promote changes in the parameters of growth and yield of sorghum in order to change the optimum harvest point. The isolated effects of the factors showed that the yield of stalks, one of the most important indicators for ethanol production, presented a higher average with application of 1.5RD (165-120-180 kg of NPK ha-1). Harvesting times did not differ. However, the economic evaluation revealed the impracticability of the fertilization practice, due to the high productivity obtained in 0RD. Due to the high incidence of Ergot disease, the content of sucrose (Pol), RTS, SR and the other technological variables were affected. However, there was an indication that the fertilization influenced the maturation in order to promote changes at the optimum harvest point, highlighting the 1,0RD as the best NPK contribution, and the cutting season at 120DAE as the best indicated for the tested cultivar. Due to the high dry matter production, Malibu 5010 sorghum hybrid accumulated NPK in the order of N <K <P (319.89; 272.53; 28.59 kg ha-1, respectively), without significant differences between the applied doses. The nutritional efficiency was higher in the treatments with lower doses of NPK, and the efficiency of use (EUt) was one of the indices that better allowed to evaluate the influence of soil fertility on the performance of sweet sorghum. The fertility of areas cultivated with sugarcane can be considered medium and in the process of construction, which would allow responses of sorghum to the application of nutrients.
Effects of fertilization in the industrial yield of sweet sorghum cultivation in improved fertility soil
Keywords: Nutrição de plantas; NPK; Bioenergia; Plant nutrition; Bioenergy; Nutrición de plantas; Bioenergía; Sorghum bicolor; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO